Role of Accounting Information to Control Adverse Selection - Apriliza, Yafika; Nur Amalia, Syahamah; Muda, Iskandar (Universitas Muhammadiyah Surabaya, 2024)
This journal article explores the role of accounting information in controlling adverse selection in financial markets. This study emphasizes the important role of accounting information transparency, disclosure, and regulatory frameworks in mitigating the risks associated with adverse selection. By providing reliable and timely accounting information, accounting practices help reduce information asymmetry among market participants, thereby minimizing adverse selection. Investor confidence is increased through access to high-quality accounting information, resulting in more informed decision making and reduced adverse selection. The research method used in writing this article is a qualitative method. This research uses a qualitative research approach using a scoping review approach. This research underscores the important role of accounting information and fair practices facilitated by effective accounting systems in overcoming the challenge of adverse selection. Overall, this research contributes to the understanding of how accounting information plays an important role in managing adverse selection and enhancing integrity in financial markets. Keywords: Accounting Information, Information Asymmetry, Adverse Selection